COMPARATIVE STUDY OF FP - GROWTH AND APRIORI IN GROCERY ANALYSIS - Adi, Ahmad Cahyono (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: The growing business environment causes the business world to create in order to continue to survive, one of which is by increasing sales. One way is to use the data approach. One method of data approach that is widely used is Market Basket Analysis. This study uses the Market Basket Analysis method with the a priori algorithm and FP-Growth. Grocery dataset analysis using two algorithms, Apriori and FP-Growth using a minimum support parameter of 0.45, has results sorted by the top 10 associations with the best confidence value. The association with the highest support value found is "Whole Milk -> Other Vegetables" with a support value of 0.0748347737. The analysis concludes that both algorithms produce the same association "Other Vegetables -> Whole Milk" with a Support value of 0.0748347737.             Keywords: apriori; FP-Growth; market basket analysis.  Abstrak : Lingkungan bisnis yang semakin berkembang menyebabkan dunia bisnis harus berkreasi agar dapat terus bertahan, salah satunya dengan cara meningkatkan penjualan. Salah satu caranya adalah dengan menggunakan pendekatan data. Salah satu metode pendekatan data yang banyak digunakan adalah Market Basket Analysis. Penelitian ini menggunakan metode Market Basket Analysis dengan algoritma apriori dan FP-Growth. Analisis dataset grosir menggunakan dua algoritma, Apriori dan FP-Growth dengan menggunakan parameter support minimum 0,45, memiliki hasil yang diurutkan berdasarkan 10 asosiasi teratas dengan nilai confidence terbaik. Asosiasi dengan nilai support tertinggi yang ditemukan adalah “Whole Milk -> Other Vegetables” dengan nilai support sebesar 0,0748347737. Analisis menyimpulkan bahwa kedua algoritma tersebut menghasilkan asosiasi yang sama “Other Vegetables -> Whole Milk” dengan nilai Support sebesar 0,0748347737. Kata Kunci: apriori; FP-Growth; market basket analysis